PENGARUH OVERVALUED EQUITIES TERHADAP TARIF AUDIT DENGAN MANAJEMEN LABA SEBAGAI VARIABEL PEMODERASI (Studi Empiris Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2012) - Surya Pramudyatama, Renaldo; Pamudji, Sugeng (Diponegoro Journal of Accounting, 2014)
The purpose of this study was to examine the effect on audit fees overvalued equities with earnings management as a moderating variable. This study uses the variable Rate Audit as the dependent variable, the dependent variable is measured using the cost index of financial statements in accordance professional manufacturing company. Overvalued equities are used as independent variables, overvalued equities can be determined by using three proxies, the Price Earning Ratio (PER), Price Book Value (PBV), and the Abnormal Return (ABnRET). This study also uses earnings management as a moderator variable, determined by earnings management In addition, this study also adds four control variables, Sales Growth, Big4, ROA, and Leverage. This study used 148 manufacturing company, samples that was used were selected by purposive sampling method. After reduction with some criteria so that the samples used were 60 companies listed in Indonesia Stock Exchange (IDX) during 2010-2012. The analytical method used was Ordinary Least Squares regression (OLS). Before doing the regression test, this study tested the classical assumptions first.Results of hypothesis testing showed that Overvalued Equities positive effect on audit fees, but in contrast to the results of Price Earning Ratio (PER) expressed a negative effect on audit fees. Other results noted that Sales Growth, Big4, Leverage, ROA is positively related to the Audit Fees. While the results of Earnings Management as moderating variables revealed no significant effect on the interaction between overvalued equities with Audit Fees. Overall it can be concluded from these results that Overvalued Equities may affect audit fees but not with earnings management as a moderator variable between the two variables is expressed negatively related research. Measurement of earnings management using the modified Jones model.